2020
DOI: 10.1055/s-0040-1708542
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Count and Function during Pediatric Extracorporeal Membrane Oxygenation

Abstract: Extracorporeal membrane oxygenation (ECMO) is a form of life support used to treat neonates, children, and adults with cardiorespiratory failure refractory to conventional therapy. This therapy requires the use of anticoagulation to prevent clotting in the extracorporeal circuit, but anticoagulation also increases the risk of bleeding on ECMO. Both bleeding and thrombosis remain significant complications on ECMO and balancing these risks is challenging. Acquired platelet dysfunction is common during ECMO and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 75 publications
0
19
1
Order By: Relevance
“…A combination of the circuit, which induces PLT adhesion and activation, and initial hemodilution that may occur during and shortly after cannulation can lead to thrombocytopenia. Studies of neonates demonstrated drops in PLT counts ranging from 25% to 60% shortly after cannulation, 19,20 whereas pediatric patients, with a larger baseline circulating blood volume and less hemodilution, have been reported to drop their PLT count by approximately 30% 21 …”
Section: Platelet Transfusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of the circuit, which induces PLT adhesion and activation, and initial hemodilution that may occur during and shortly after cannulation can lead to thrombocytopenia. Studies of neonates demonstrated drops in PLT counts ranging from 25% to 60% shortly after cannulation, 19,20 whereas pediatric patients, with a larger baseline circulating blood volume and less hemodilution, have been reported to drop their PLT count by approximately 30% 21 …”
Section: Platelet Transfusionsmentioning
confidence: 99%
“…Studies of neonates demonstrated drops in PLT counts ranging from 25% to 60% shortly after cannulation, 19,20 whereas pediatric patients, with a larger baseline circulating blood volume and less hemodilution, have been reported to drop their PLT count by approximately 30%. 21 To correct thrombocytopenia, PLT transfusions are recommended, although the evidence supporting the recommendations is based on expert opinion alone. ELSO guidelines recommend transfusion of PLTs to keep the count greater than 80 × 10 9 /L in nonbleeding patients or 100 × 10 9 /L in bleeding patients.…”
Section: Platelet Transfusionsmentioning
confidence: 99%
“…While renal insufficiency was recorded, it was not associated with mortality in this cohort.The RESP score utilized ELSO registry data from 2000 to 2012 to develop a model for predicting hospital survival at the initiation of ECMO for respiratory failure 98. The authors identified12 pre-ECMO variables (age, immunocompromised status, mechanical ventilation duration before ECMO initiation, acute respiratory failure diagnosis group, CNS dysfunction, acute non-pulmonaryassociated infection, neuromuscular blocking agent use, nitric oxide use, bicarbonate infusion, cardiac arrest, PaCO2, and peak inspiratory pressure) associated with survival and developed a scoring system that predicted survival, with a step-wise decline in survival by RESP score risk class (ranging from 92% at RESP class I to 18% at RESP class V). While renal dysfunction was initially identified for potential inclusion, it was not independently predictive of survival and thus not included in the final RESP score.…”
mentioning
confidence: 99%
“…In the present issue, Cashen et al provide an overview of hemostatic challenges during pediatric ECMO with a focus on platelet count and function, and the association with bleeding risk. 14 The review points to the important fact that platelet function testing is very challenging in neonatal and pediatric patients due to the relatively large volume of blood needed for this analysis and the lack of standardization of platelet function tests, especially in children. As a consequence, a paucity of evidence exists on platelet function during pediatric ECMO support, and platelet counts are most often the measure used to monitor the role of platelets and judge the need for platelet transfusions during ECMO.…”
mentioning
confidence: 99%
“…Finally, Cashen et al discuss future needs for optimization of patient management during ECMO in light of the critical need of reducing the risk of bleeding and thromboembolism during pediatric ECMO support. 14 Intraventricular hemorrhage is a severe complication of premature birth and affects up to 22% of extremely low birth weight neonates. 15 Grevsen et al present a systematic review and meta-analysis of the role of platelet counts and other platelet indices in premature neonates with intraventricular hemorrhage.…”
mentioning
confidence: 99%